SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN SISWA BARU DAN PENJURUSAN PADA SEKOLAH MENENGAH KEJURUAN(SMK) - Hadi Sucipto; Kusrini .; Hanif Al Fatta (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2017)
Many available majors at the level of vocational schools make students dificult to determine the appropriate majors with his ability. Most students just followed their friends to choose themajors that can cause students feel does not match after entering the majors. Therefore we needa decision support system that can perform calculation of values, abilities and interests owned bythe students to help determine the appropriate majors. The purpose of this study is to apply theDecision Tree algorithm model in grading each department based on the criteria of each departmentand apply methods SAW (Simple Additive weighting) in a sort highest to the lowest value in eachdepartment.